Economics of human resources - Strotz, R...[et.al.] (Amsterdam, 1963)
In this book an attempt is made to give a systematic account of the Economics of Human Resources as a branch of Economic Science. In this study, a basic element is the Economics of Education, and large portions of the present work make an organized study of this topic. The study of these subjects, in spite of their great interest, is in its earliest stages. The book has been divided into two parts. The first part deals with the supply of labor, the second with its demand. In the supply of labor, an analysis is made of the factors affecting quantity and quality of the labor force. The study of the demand for labor includes two aspects. First, the impact of the quantity and quality of labor on production is studied. Second, the effect of the volume of production on the amount and char acteristics of labor demanded is analyzed.
Keywords: Economics